PENGARUH JUMLAH PENDUDUK, PENDUDUK MISKIN DAN PENGANGURAN TERBUKA TERHADAP PERTUMBUHAN EKONOMI DI KOTA BANJARBARU - ERLINA ERLINA; LINA SUHERTY (PPJP Universitas Lambung Mangkurat, 2019)
Erlina (2019) Influence of Population, Number of Poor Population, and Open Unemployment on Economic Growth in Banjarbaru city. Advisor : Lina Suherty, SE, MP. This Research was conducted to (1) analyze the Influence of Population, Poor Population, and Open Unemployment on Economic Growth in Banjarbaru city ; (2) to find out what factors are most dominant in influencing economic growth ini the city of Banjarbaru. This research was conducted in the city of Banjarbaru with data from the central Kalimantas Statistics Agency that can be used indata processing. Data is processed using multiple regression analysis (Multiple Regression Analysis) with F Test and T Test. The result of this study prove a positive relationship betwaan the level of population and economic growth. This shows that the greater the level of population will increase economic growth in the city of Banjarbaru.Key word : Economic Growth, Poverty, Open Unemployment